Molecular simulation study on hydrogen gas via quantum description - Gan, Hong En (2009)
The project comprises 4 parts. In part 1, the author was required to understand the various important concepts of quantum mechanics and then plot the contour plot of hydrogenic atoms. In part 2, the author was then asked to verify the validity of percentage electron probability densities published in journal article. This is done by using the Mathematica software. In part 3, the author needs to understand the Monte Carlo simulation method and generate a three-dimensional simulation module for hydrogen atom consists of a nucleus and an electron. The nucleus and the electron interact through Coulombic potential. The simulation was generated using Eclipse software and Etomica support files. Next, in part 4, the author was required to understand the statistical thermodynamics and then generate a one-dimensional harmonic oscillator simulation module. The harmonic oscillator can be used to predict the behavior of electron.